Teaching Approaches and Bridging the Classroom-Reality Gap in Higher Education - Abdullahi, Nimota Jibola Kadir (Asian Journal of Assessment in Teaching and Learning, 2025)
In today's ever-changing modern world, traditional educational settings often struggle to keep pace with the evolving needs of the workforce. As academic institutions strive to equip students with practical skills, there is a growing recognition of the need to connect classroom learning to real-world situations. This study examined the relationship between teaching approaches and bridging the classroom-reality gap in higher education in Nigeria. In particular, it draws on Experiential Learning Theory (ELT), which posits that meaningful learning is achieved through direct experience, reflection, and active engagement rather than passive absorption of information. By emphasizing learning as a process where knowledge is created through the transformation of experience, ELT underpins the study’s exploration of experiential learning as a key pedagogical strategy. A structured survey was used to gather quantitative data for the study. The lecturers in Nigeria's public universities were the target population. SPSS and SmartPLS tools were used to analyze the data. The findings suggest that effective management of teaching approaches such as experiential learning, technology integration, and career preparation in higher education institutions significantly influences the gap between the classroom and reality. The study's findings show a statistically positive and significant association between experiential learning, technology integration, career preparation approaches, and bridging the classroom-reality gap in higher education. By bridging the gap between theoretical knowledge and practical implementation, the findings of this study contribute to the ongoing dialogue on pedagogical practices in higher education and workforce development, aiming to better prepare students for the challenges they will face in their future careers.